Riots and the window of opportunity for coup plotters: Evidence on the link between urban protests and coups d'état - Lena Gerling (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2017)
This paper investigates the impact of urban protests on coup attempts in a sample of 39 Sub- Saharan African countries for the period 1990 to 2007. Widespread public discontent, especially when occurring in urban centers, can act as a trigger of coups d'état in autocratic regimes by opening a window of opportunity for leadership removals by the ruling elite. The main difficulty in testing this relationship is that public revolts are rarely exogenous to coup risk. To address this problem, variation in rainfall is used to create an instrument for urban protests. The results show that rainfall-related popular uprisings in urban areas increase the likelihood of a coup attempt and thus help to solve the collective-action problems associated with coup plots.
Keywords: C26; D74; P16; 330; coup d'état; public protest; regime change; autocracy